1996
DOI: 10.1128/aac.40.2.413
|View full text |Cite
|
Sign up to set email alerts
|

The guanine nucleoside analog penciclovir is active against chronic duck hepatitis B virus infection in vivo

Abstract: Ducks congenitally infected with duck hepatitis B virus (HBV) were treated with the antiviral guanine nucleoside analog penciclovir for 4 weeks at a dose of 10 mg/kg of body weight per day. The effects of treatment on viremia and intrahepatic viral genome replication, transcription, and translation were examined. In seven of eight penciclovir-treated ducks, viremia was barely detectable after a week of treatment. After 4 weeks of treatment, molecular hybridization studies showed that intrahepatic viral DNA, RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…Previously, famciclovir was effective in reducing the intrahepatic replication of duck hepatitis B in vivo [19]. Famciclovir was the first nucleoside analogue shown to significantly reduce the level of viral covalently closed circular DNA species of duck hepatitis B virus, the key intermediate typically resistant to nucleoside analogue therapy [20]. In humans, famciclovir at a dosage of 500 mg three times a day for 16 weeks had a dose-dependent suppressive effect on HBV DNA replication [21].…”
Section: Discussionmentioning
confidence: 98%
“…Previously, famciclovir was effective in reducing the intrahepatic replication of duck hepatitis B in vivo [19]. Famciclovir was the first nucleoside analogue shown to significantly reduce the level of viral covalently closed circular DNA species of duck hepatitis B virus, the key intermediate typically resistant to nucleoside analogue therapy [20]. In humans, famciclovir at a dosage of 500 mg three times a day for 16 weeks had a dose-dependent suppressive effect on HBV DNA replication [21].…”
Section: Discussionmentioning
confidence: 98%
“…Penciclovir inhibits duck HBV replication in vitro and in animal experiments [2,3]. Recent clinical trials showed famciclovir to be well-tolerated and to suppress HBV replication in patients with chronic HBV infection [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Famciclovir has been approved for treatment of acute herpes zoster and herpes simplex virus infections. Penciclovir is also a potent inhibitor of the HBV DNA polymerase [2] and has been shown to inhibit HBV replication in vitro and in vivo [3].The aim of this pilot study was to evaluate the safety and antiviral and clinical effects of famciclovir alone and when used in combination with IFN-a in patients with chronic HBV infection who did not respond to previous therapy with IFN alone. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is most likely caused by intracellular persistence of circular HBV CCC DNA [90,91] and persistence of virus in nonhepatocyte reservoirs [72]. Monotherapy with these new antiviral agents is unlikely to be sufficient for the eradication of HBV infection in the majority of patients.…”
Section: Combination Therapymentioning
confidence: 99%